Determinan produktivitas tenaga kerja industri kopi bubuk di Kabupaten Muara Enim - Satri Rahmadi; Yunisvita Yunisvita; Imelda Imelda (Department of Development Economics, Universitas Sriwijaya, 2018)
This study aimed to examine the affect of the wage, age, and number of dependents to labor productivity of coffee powder business. The study was done in Muara Enim regency by using primary data with 65 respondents as the sample from 181 people as the population. The technique of selecting the data was survey method with random sampling method. The technique of analyzing the data that was used of this study was multiple linear regression analysis with OLS method. The results of this study were: 1. The wage affected positive impact and was significant to productivity. 2. Age affected positive impact and was significant to productivity. 3. Number of dependents affected positive impact but was not significant to productivity. The most dominant variable of this study was age. So, the variation of all independent variables could explain the total number of variation of productivity was 93%.